2007
DOI: 10.1007/s10620-007-9974-2
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoidosis in Patients with Celiac Disease

Abstract: In this cohort of patients with celiac disease, there was a significantly increased risk of sarcoidosis when compared with the American white population. This further strengthens prior associations that have been made suggesting a shared mechanism behind the etiologies of celiac disease and sarcoidosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 29 publications
0
10
0
3
Order By: Relevance
“…No data are available in this study on endomysial or tissue transglutaminase antibody serology. A more recent report in a large cohort of patients found a standardised morbidity ratio adjusted for age and sex of 36.8 (95% CI 26.7 to 50.9) for a diagnosis of sarcoidosis in 10 out of 866 patients with coeliac disease 18. If the association is real, it would be consistent with a defect in antigen processing in both diseases, because overexpression of HLA class II molecules in coeliac disease may predispose to sarcoidosis.…”
Section: Discussionmentioning
confidence: 97%
“…No data are available in this study on endomysial or tissue transglutaminase antibody serology. A more recent report in a large cohort of patients found a standardised morbidity ratio adjusted for age and sex of 36.8 (95% CI 26.7 to 50.9) for a diagnosis of sarcoidosis in 10 out of 866 patients with coeliac disease 18. If the association is real, it would be consistent with a defect in antigen processing in both diseases, because overexpression of HLA class II molecules in coeliac disease may predispose to sarcoidosis.…”
Section: Discussionmentioning
confidence: 97%
“…[7] On the other hand, the association between sarcoidosis and celiac disease, an autoimmune inflammatory disorder induced by the antigenic properties of gluten, supports the view of defective antigenic processing by the immune system. [14] The underlying pathogenetic mechanisms of JS are poorly understood. It has been suggested that the disease occurs mainly when a genetically predisposed host is exposed to a persistent, poorly degradable environmental antigenic stimulus.…”
Section: Etiology and Immunopathogenesismentioning
confidence: 99%
“…A possible increased risk of venous thromboembolism among adult celiac patients may occur [175]. Celiac disease may be linked to sarcoid [176,177], perhaps through common haplotypes [178]. Diffuse lung disease occurs in celiac disease.…”
Section: Pulmonary Diseasesmentioning
confidence: 99%